2012
DOI: 10.1037/a0026585
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements during scene recollection have a functional role, but they are not reinstatements of those produced during encoding.

Abstract: Current debate in mental imagery research revolves around the perceptual and cognitive role of eye movements to "nothing" (Ferreira, Apel, & Henderson, 2008; Richardson, Altmann, Spivey, & Hoover, 2009). While it is established that eye movements are comparable when inspecting a scene (or hearing a scene description) as when visualizing it from memory (Johansson, Holsanova, & Holmqvist, 2006), the exact purpose of these eye movements remains elusive. Are eye movements during recall purely epiphenomenal or do t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
146
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(170 citation statements)
references
References 84 publications
16
146
1
1
Order By: Relevance
“…For example, executing eye-movements during VSWM tasks disrupts visuospatial working memory more than other types of distractor tasks (Lawrence, Myerson, & Abrams, 2004;Pearson & Sahraie, 2003). Similarly, eye-movements to the locations of remembered stimuli are often observed during recall of spatial information (Brandt & Stark, 1997;Johansson, Holsanova, Dewhurst, & Holmqvist, 2012;Spivey & Geng (2001) In contrast, others have argued that VSWM is reliant on covert spatial attention (the ability to attend to locations without actually looking at them), rather than plans for eyemovements. In support of the covert attention proposal, Awh and colleagues (1998) found that reaction times were faster when targets appeared at locations held in working memory, and that spatial working memory was poorer when participants were prevented from attending to these memorized locations during the retention interval (see also Awh & Jonides, 2001).…”
Section: Introductionmentioning
confidence: 96%
“…For example, executing eye-movements during VSWM tasks disrupts visuospatial working memory more than other types of distractor tasks (Lawrence, Myerson, & Abrams, 2004;Pearson & Sahraie, 2003). Similarly, eye-movements to the locations of remembered stimuli are often observed during recall of spatial information (Brandt & Stark, 1997;Johansson, Holsanova, Dewhurst, & Holmqvist, 2012;Spivey & Geng (2001) In contrast, others have argued that VSWM is reliant on covert spatial attention (the ability to attend to locations without actually looking at them), rather than plans for eyemovements. In support of the covert attention proposal, Awh and colleagues (1998) found that reaction times were faster when targets appeared at locations held in working memory, and that spatial working memory was poorer when participants were prevented from attending to these memorized locations during the retention interval (see also Awh & Jonides, 2001).…”
Section: Introductionmentioning
confidence: 96%
“…Johansson, Holsanova, & Holmqvist, 2006;Martarelli & Mast, 2011;Martarelli, Chiquet, Laeng, & Mast, 2016;Richardson & Spivey, 2000;Richardson & Kirkham, 2004;Spivey & Geng, 2001;Wantz, Martarelli, & Mast, 2016). Moreover, it has been shown that returning the eyes to spatial locations where the stimuli were previously encoded facilitates memory retrieval (Johansson, Holsanova, Dewhurst, & Holmqvist, 2012;Johansson & Johansson, 2014;Laeng & Teodorescu, 2002;Laeng, Bloem, D'Ascenzo, & Tommasi, 2014;Scholz, Mehlborn, & Krems, 2016). However, previous research investigating the "looking at nothing phenomenon" always presented visual information during encoding.…”
mentioning
confidence: 99%
“…The principal function of eye movements is to bring details of our visual environment into focus, allowing for conscious perception. However, our eyes do not only move to extract information from the visual world: previous studies already showed that inspecting a mental image in the mind's eye (e.g., inspecting an imagined house from the bottom to the top) leads to corresponding eye movements in the physical world (Laeng & Teodorescu, 2002;Spivey & Geng, 2001), and eye movement patterns during memory retrieval resemble those during real-time exploration (Johansson, Holsanova, Dewhurst, & Holmqvist, 2012;Johansson & Johansson, 2014;Martarelli & Mast, 2013;Micic, Ehrlichman, & Chen, 2010). The studies reported here suggest that the eyes also ''inspect'' abstract concepts such as a mental number line, and that they ''act out'' spatial relations of our thoughts.…”
Section: Discussionmentioning
confidence: 99%